Imagining Europe in Times of War and Crises
XVII, 152 p. 9 illus., 7 illus. in color.
Keywords: This book aims to explore the perceptions of the EU integration by the young population in its “periphery”. It thereby bridges the gap between perceptions studies, youth studies, and the center-periphery conceptual framework. The chapters in the volume make use of data generated from focus group meetings with university students aged between 18-30 (which is the age range generally used by the European Social Survey to group young citizens) in Romania, Kosovo, Albania, North Macedonia, Georgia and Turkiye.